Are dual purpose crops a breeding priority? The case of cassava - Newby, Jonathan (CGIAR Initiative on Market Intelligence, 2024)
The article explores the concept of dual-purpose crops, specifically focusing on cassava, and the importance of breeding these crops to meet diverse needs. It examines whether these crops should be prioritized in breeding efforts, considering the demand for both food and industrial use. By aligning breeding programs with market segments and farmer requirements, the article discusses the value of prioritizing traits that serve multiple purposes. Ultimately, it emphasizes the need for collaboration among researchers, farmers, and other stakeholders to optimize crop development for broader applications.